Assessment of Quality of Groundwater in Kandarvakottai and Karambakudi Areas of Pudukkottai District, Tamilnadu, India - D. Ilangeswaran; R. Kumar; D. Kannan (E-Journal of Chemistry)
Various samples of groundwater were collected from different areas of Kandarvakottai and Karambakudi of Pudukkottai District, Tamilnadu and analyzed for their physicochemical characteristics. The results of this analysis were compared with the water quality standards of ISI, WHO and CPHEEO. In this analysis the various physicochemical parameters such as pH, electrical conductivity, turbidity, total dissolved solids, Cl-, F-, SO42-, PO43-, NO3-, NO2-, CN-, Nas+, K+, NH3, Mn, Fe, Ca & Mg hardness etc., were determined using standard procedures. The quality of groundwater samples were discussed with respect to these parameters and thus an attempt were made to ascertain the quality of groundwater used for drinking and cooking purposes in and around Kandarvakottai and Karambakudi areas.